Investigation of transfer pricing models among a network firm for a distributed product - Liang, Baozhu (University of Ottawa (Canada), 2005)
This work investigates transfer pricing models among network-manufacturing firms for a distributed product. The particularities of the models are: instead of each company trying to maximize individually the value added to its supply chain in which it is embedded, The models propose to maximize the value added by the network-companies in the global supply chain. Under specific assumptions on the nature of production, cost and value functions in typical production/distribution companies, it optimizes the supply chain structure for network-companies, distributed in one economic region. We calculate the transfer price and share the value added between the networked firms by two approaches: resource-based approach and efficiency-based approach. The models are formally defined, optimally formulated, and solved.
Keywords: Engineering, System Science.